USING METHYL UREA AS INHIBITOR FOR THE CORROSION OF CARBON STEEL IN 1M HYDROCHLORIC ACID MEDIUM - Al-Mammar, Dunya (Iraqi Journal of Science, 2024)
The corrosion behaviour of carbon steel in 1M HCl solution containing variousconcentration of methyl urea range (10-35×10-2)M at temperature range (285-313)K was investigated. The corrosion inhibitive action of methyl urea on carbonsteel was studied using weight loss measurement and atomic absorption analysis tofind the amounts of dissolved metal in acidic solution in presence and absence ofmethyl urea. The results showed that urea caused protection efficiency reached to82% when (10-3)M methyl urea concentration was used. The coverage () of metalsurface by methyl urea could be obtained from the rate of corrosion in the presenceand absence of methyl urea in the acid solution. Results obtained by gravimetric andatomic absorption are in good agreement. A linear relationship was found to existbetween the value of (C/) and the corresponding methyl urea concentration (C)indicating that the inhibition action occurs via adsorption mechanism. Changes inthe free energy, enthalpy and entropy associated with methyl urea adsorption havebeen determined. Apparent energies of activation have been calculated for thecorrosion process of iron in the acid from corrosion rates and Arrhenius plots.